2008
DOI: 10.1103/physrevb.77.235208
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and defect reactions between donors, C, and vacancies in Ge. II. Atomistic calculations of related complexes

Abstract: Electronic structure calculations are used to study the stability, concentration, and migration of vacancydonor ͑phosphorus, arsenic, and antimony͒ complexes in germanium, in the presence of carbon. The association of carbon with mobile vacancy-donor pairs can lead to energetically favorable and relatively immobile complexes. It is predicted that the complexes formed between lattice vacancies, carbon, and antimony substitutional atoms are more stable and less mobile compared to complexes composed of vacancies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
96
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 52 publications
7
96
0
Order By: Relevance
“…This has been concluded from self-and foreign-atom diffusion studies 7,21,22,[27][28][29][30] and confirmed by atomistic calculations. 15,23,[30][31][32][33] In particular, the simultaneous diffusion of self-and dopant atoms in isotopically controlled Ge heterostructures have revealed that vacancies in Ge are mainly doubly negatively charged under intrinsic and n-type doping conditions. 7,34 However, the preferred charge state of V under p-type doping is not known.…”
Section: B Motivation Of Diffusion Model and Numerical Simulationsmentioning
confidence: 99%
“…This has been concluded from self-and foreign-atom diffusion studies 7,21,22,[27][28][29][30] and confirmed by atomistic calculations. 15,23,[30][31][32][33] In particular, the simultaneous diffusion of self-and dopant atoms in isotopically controlled Ge heterostructures have revealed that vacancies in Ge are mainly doubly negatively charged under intrinsic and n-type doping conditions. 7,34 However, the preferred charge state of V under p-type doping is not known.…”
Section: B Motivation Of Diffusion Model and Numerical Simulationsmentioning
confidence: 99%
“…The efficacy of the approach used in the present study has been recently established by comparing with experimental results. [25][26][27][28][29] …”
Section: A Details Of Calculationsmentioning
confidence: 99%
“…Sn has been found to diffuse in Ge with an activation enthalpy in the range of 2.9-3.26 eV, which can be attributed to a V-mechanism of diffusion. 12 In this context we now investigate the stability of SnV pairs as well as Sn 2 V and SnV 2 complexes in otherwise pure Ge and in Si for comparison. The cluster configurations have previously been reported.…”
mentioning
confidence: 99%
“…The significance of vacancies ͑V͒ in the diffusion and defect processes in Ge ͑such as those caused by radiation damage͒ has been the subject of numerous studies. 12,13 The aim of the present work is thus twofold: first, to establish an effective approach to model the structure of Sn 1−x Ge x alloys of high Sn content and second to study the structure of Sn n V m complexes in Ge and thereby demonstrate that the computational method also generates useful results at lower Sn concentrations.…”
mentioning
confidence: 99%